Pemahaman dan Pendampingan Penataan Batas Wilayah Administratif dengan Metode Kartometrik di Kelurahan Tataaran satu, Kecamatan Tondano Selatan, Kabupaten Minahasa: Understanding and Assistance in the Delimitation of Administrative Boundaries Using the Cartometric Method in Tataaran Satu Village, South Tondano District, Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
The Community Partnership Program (PKM) implemented in Tataaran Satu Urban Village, South Tondano District, Minahasa Regency, focuses on understanding and facilitating the delineation of administrative boundaries using the cartometric method. This initiative addresses issues such as discrepancies between administrative maps and field conditions, limited public understanding of legitimate territorial boundaries, and delays in spatial data updates that may lead to land disputes and inaccuracies in development planning. Through a series of socialization activities, mentoring sessions, and technical training, the implementing team successfully produced an updated and accurate administrative map that reflects actual field conditions. The program also enhanced the understanding of both local communities and village officials regarding the importance of administrative boundary clarity. The outcomes of this program include not only an official reference map for spatial management but also a scientific publication as an academic contribution. Overall, this PKM project contributes to boundary conflict prevention, improved development planning quality, and strengthened public service effectiveness at the urban village level.